The ILCA/NLPU on-farm alley farming project: Considerations on data collection and evaluation - Atta-Krah, A.N. (International Livestock Centre for Africa, 1986)
Presents ILCA's on-farm alley farming research activities in the humid zone of Nigeria. Discusses the problems in data collection and analysis, soil variability, management variability, problems of labour estimation, land clearing & preparation, planting & management, tree prunning & utilization and monitoring & evaluation procedures.